How does BMI correlate with menarche onset? Evidence from the Italian HBSC cross-sectional study - Domitilla Marconi; Dario Lipari; Andrea Pammolli; Paola Dalmasso; Paola Nardone; Alessio Vieno; Rita Simi; Giacomo Lazzeri (BMC Women's Health)
Abstract Background Menarche is an important period in a female’s life; its time of onset may depend on various factors and could correlate with the development of diseases in adulthood. Our study aims to investigate the relationship between body mass index and age at onset of menarche; Methods We used a unique standardized national dataset on adolescent girls participating in the Italian Health Behaviour in School-aged Children Study. Two independent nationally representative survey datasets: one on 15-year-olds (n = 6505, year 2017/2018) and one on 11-year-olds (n = 6548, year 2013/2014) were analysed. The survey instrument was the self-report questionnaire. Median age at menarche and 95% confidence intervals were estimated through Kaplan–Meier analysis. Hierarchical models assessed the relationship between BMI and age at menarche; Results Region-level median age at menarche ranged between 12 years/5 months and 13 years/4 months. Region-level prevalence of overweight among 15-year-old girls ranged between 6% and 24%. Age at menarche was inversely associated with individual BMI (unstandardized regression coefficient beta=-0.81; 95% CI, -0.92 to -0.70). Individual-level and class-level measures of BMI accounted for 215.2% of the region-level variance in age at menarche; Conclusions The results show that girls who were overweight during childhood went through early puberty. Further investigation needs to assess a possible cause-effect relationship.